Prediksi Safety Stock Menggunakan Algoritma Support Vector Regression Dengan Optimasi Hyperparameter - Hardika, Rianindya Chandra; Anggara, Fiky; Abrori, Mohammad Ahmad Maidanul (STMIK Banjarbaru, 2026)
Inventory management plays an essential role in ensuring smooth supply chain operations and preventing both stockouts and overstocking. One effective approach to determining the appropriate level of safety stock is the use of machine learning–based prediction methods. This study aims to predict safety stock values using the Support Vector Regression (SVR) method with hyperparameter optimization through GridSearch. The dataset used is a public bike rental dataset, which includes variables such as time, weather, season, and holidays. The research stages include data preprocessing, Exploratory Data Analysis (EDA), implementation of the SVR model, and model performance evaluation using MAE, MAPE, and R² metrics. The performance of the Support Vector Regression (SVR) algorithm with a Radial Basis Function (RBF) kernel and optimal parameters demonstrates strong predictive accuracy. Based on the Mean Absolute Percentage Error (MAPE), the model achieved prediction accuracies of 83.8%, 80.1%, and 81.7% on the training, validation, and testing datasets, respectively, indicating its effectiveness in modeling non-linear data. This model is capable of generating more precise safety stock predictions, thereby supporting decision-making in inventory planning and reducing the risk of stock shortages.Keywords: Safety Stock; Support Vector Regression; Demand Prediction; Hyperparameter Tuning AbstrakManajemen persediaan memiliki peran penting dalam menjaga kelancaran rantai pasok dan menghindari kekurangan maupun kelebihan stok. Salah satu pendekatan yang efektif untuk menentukan jumlah safety stock adalah dengan memanfaatkan metode prediksi berbasis machine learning. Penelitian ini bertujuan untuk memprediksi nilai safety stock menggunakan metode Support Vector Regression (SVR) dengan optimasi hyperparameter tuning melalui teknik GridSearch. Data yang digunakan merupakan dataset publik penyewaan sepeda yang mencakup variabel waktu, cuaca, musim, dan hari libur. Tahapan penelitian meliputi preprocessing data, analisis Exploratory Data Analysis (EDA), penerapan model SVR, serta evaluasi kinerja model menggunakan metrik MAE, MAPE, dan R². Hasil penelitian menunjukkan bahwa model SVR dengan kernel RBF dan parameter optimal menghasilkan tingkat akurasi prediksi yang baik. Berdasarkan nilai MAPE, model mencapai akurasi 83,8% pada data latih, 80,1% pada data validasi, dan 81,7% pada data uji, yang mengindikasikan kemampuan SVR dalam memodelkan data non-linear. Model ini mampu memprediksi kebutuhan safety stock lebih baik, sehingga dapat membantu pengambilan keputusan dalam perencanaan persediaan dan mengurangi risiko kekurangan stok.Kata kunci: Safety Stock; Support Vector Regression; Prediksi Permintaan; Hyperparameter Tuning